Chinese Commodity Imports in Ghana and Senegal: Demystifying Chinese Business Strength in Urban West Africa - Laurence Marfaing; Alena Thiel (German Institute of Global and Area Studies (GIGA), 2011)
Since the beginning of the twenty-first century, independent entrepreneurial migrants from China have been increasingly flocking to Africa in search of greener pastures. This paper scrutinizes the empirical foundations of the increasingly hostile discourses of African traders regarding the alleged encroachment of the West African urban market space by Chinese petty entrepreneurs. Based on indepth ethnographic fieldwork and interviews, we aim to demystify this common allegation by exploring the diversity of influx channels through which Chinese commodities, said to create unfair and existential competition, come to the African continent. Our analysis of trade trajectories shows that Chinese products were coming to Africa long before the arrival of independent Chinese migrants at the beginning of the twenty-first century. Statistical evidence further supports our stance that Chinese entrepreneurs still represent a minority group in the import of cheap China goods into Ghana and Senegal.
Keywords: D43; D85; F14; F22; L14; O24; P45; Z1; 330; international trade; consumer goods; imperfect competition; migration; social networks; China; Africa; Konsumgut; Außenhandel; China; Import; Unternehmer; Chinesen; Ghana; Senegal